Dr. Adam Lowenstein - Lowenstein, Adam (DEEPPLANE™ surgeon registry, 2026)
Surgeon profile record for Dr. Adam Lowenstein, practicing in Santa Barbara, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
CC-BY-4.0 licensed; published by DEEPPLANE™
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; santa barbara